Improved Voltage Control for the Electric Vehicle Operation in V2H Mode as an Off-Line UPS in the Context of Smart Homes - Monteiro, Vitor; Catalao, Joao; Sousa, Tiago; G. Pinto, J.; Mezaroba, Marcello; L. Afonso, Joao (EAI Endorsed Transactions on Energy Web, 2019)
As a contribution for sustainability, electric vehicles (EVs) are seen as one of the most effective influences in the transport sector. This paper proposes an improved voltage control of the EV operating as uninterruptible power supply (UPS) in smart homes. With the EV plugged-in into the smart home, it can act as an off-line UPS protecting the electrical appliances from power grid outages. The foremost advantages of the proposed voltage control strategy are comprehensively emphasized, establishing a comparison with the classical approach. Aiming to offer a sinusoidal voltage for linear and nonlinear electrical appliances, a pulse width modulation with a multi-loop control scheme is used. A Kalman filter is used for decreasing significantly the time of detecting power outages and, consequently, the transition for the UPS mode. The computer simulations and the acquired experimental results validate the proposed strategy in different conditions of operation.
Keywords: Electric Vehicle; Bidirectional Converter; Uninterruptible Power Supply; Kalman Filter; Smart Home